GlycA, a marker of protein glycosylation, is related to albuminuria and estimated glomerular filtration rate: the ELSA-Brasil study - Silvia M. Titan; Roberto Pecoits-Filho; Sandhi M. Barreto; Antônio Alberto Lopes; Isabela J. Bensenor; Paulo A. Lotufo (BMC Nephrology, 2017)
Abstract Background Systemic inflammation has been implicated in several chronic diseases. GlycA is a new nuclear mass resonance (NMR) spectroscopy-derived biomarker of systemic inflammation that reflects protein glycosylation. We evaluated the association of GlycA with albuminuria and eGFR in the ELSA-Brasil Study. Methods The cross-sectional association between GlycA (automated NMR LipoProfile(®) test spectra, LabCorp, Raleigh, NC), and overnight 12 h–albuminuria and CKD-EPI eGFR was evaluated among 5050 participants. Results GlycA was higher among older, women, smokers, alcohol abstemious, obese and in those with diabetes, hypertension or dyslipidemia. In addition, both eGFR and albuminuria were associated to GlycA. In linear regression, GlycA was independently associated with log albuminuria (B 0.03; 95%CI 0.02–0.04, P < 0.0001, per 1sd increase) and inversely related to eGFR (B -0.53; 95%CI -0.99 – -0.07, P < 0.02), even after adjustments including hsCRP. In logistic regression, GlycA was independently related to the risk of A2 or A3 albuminuria (OR 1.42, 95%CI 1.27–1.57, p < 0.0001, per 1sd increase), of having an eGFR < 60 ml/min/1.73m2 (OR 1.26, 95%CI 1.12–1.41, p = 0.0003, per 1 sd) or of a combined diagnosis of both conditions (OR 1.35, 95%CI 1.23–1.46, p < 0.0001, per 1 sd). In the ROC curve, GlycA had a higher AUC in comparison to hsCRP (AUC 0.67 vs. 0.62, p = 0.06) for the association with albuminuria A2 or A3. Conclusions The present study demonstrates that GlycA is associated with albuminuria and eGFR, independently of major risk factors for CKD progression, including (and with a stronger association than) hsCRP. GlycA should be further evaluated in CKD progression.